The annealing of high - level doped materials on the base of the n – and p – Si₀.₇ Ge₀.₃ solid solution under reactor irradiation - Dolgolenko, A.P. (Вопросы атомной науки и техники, 2006)
N- and p-type samples of Si-Ge solid solution with the resistivity of (4...7) 10⁻³⋅ Ohm·cm, unannealed after high-temperature
baking have been investigated. Samples were irradiated up to the fluence ~10²⁰ n⁰·cm⁻² in reactor active zone at the temperature
~500 ºC in mixed neutron field. It has been observed that in the process of reactor irradiation not only phosphorus or boron precipitation,
but the annealing of samples occurs resulting in the increase of doped substituting impurities solubility and hence in
the reduction of resistivity. It is shown that the radiated redistribution can be described by diffusion and relaxation processes.
The dose dependence on resistivity as a function of fast-pile neutron fluence was calculated and interpreted in terms of the effective
medium theory. Activation energies of the doping impurities annealing process and characteristic dimensions of defect clusters
have been defined. Исследованы образцы n- и p-типа проводимости твердого раствора кремний-германий с удельным сопротивлением (4...7) 10⁻³⋅ Ом/см, не прошедшие отжига после высокотемпературного спекания. Образцы облучались до флюенса ~10²⁰ n⁰·•cм⁻² в активной зоне реактора ВВР-М при температуре ~500 ºC в смешанном нейтронном поле. В процессе облучения наблюдались не только преципитация легирующей примеси бора и фосфора, но и увеличение их растворимости, обусловленное кластерами дефектов. Показано, что радиационное перемешивание можно описать на языке диффузионных и релаксационных процессов. Изменение удельного сопротивления в зависимости от флюенса быстрых нейтронов описано в рамках теории эффективной среды. Определены энергии активации процесса отжига легирующих примесей и характерные размеры кластеров дефектов. Досліджені зразки n- та p-типу провідності твердого розчину кремній-германій з питомим опором (4...7) 10⁻³⋅
Ом/см, що не пройшли відпал після високотемпературного спікання. Зразки опромінювались до флюєнсу ~10²⁰ n⁰·•cм⁻²
в активній зоні реактора ВВР-М при температурі ~500 ºC в змішаному нейтронному полі. В процесі опромінювання
спостерігались не тільки преципітація легуючої домішки бору та фосфору, але й збільшення їх розчинності, що
обумовлено кластерами дефектів. Показано, що радіаційне перемішування можна описати в термінах дифузійних та
релаксаційних процесів. Зміна питомого опору в залежності від флюєнсу швидких нейтронів описана в рамках теорії
ефективного середовища. Визначені енергії активації процесу відпалу легуючих домішок та характерні розміри
кластерів дефектів.